The use of portable X-ray fluorescence spectrometry to measure apparent total tract digestibility in beef cattle and sheep. (13th February 2020) - Hoffmann, Carly A; Sarturi, Jhones O; Weindorf, David C; Henry, Darren D; Ramirez- Ramirez, Hugo A; Jackson, Samuel; Ballou, Michael A; Sandes, Michael D; Bouyi, Legrand
Abstract: The use of portable X-ray fluorescence (PXRF ) spectrometry to detect external markers on processed or unprocessed cattle and sheep fecal specimens to estimate apparent total tract digestibility (ATTD ) was evaluated. Exp. 1: ruminally cannulated Angus-crossbred steers ( n = 7; BW = 520 ± 30 kg) were individually fed ad libitum for 21 d in a completely randomized design (CRD ). Markers (Cr2 O3 and TiO2 ) were placed inside the rumen twice daily (7.5 g of each marker). Fecal samples were collected twice daily from day 14 to 21. Exp. 2: crossbred wethers ( n = 8; BW = 68 ± 3 kg) were individually fed ad libitum for 21 d in a CRD. During this period, 2 g of Cr2 O3 and TiO2 were top-dressed onto the feed twice daily. Sheep were housed in metabolism crates for 5 d for total fecal collection. Concentration of markers was determined on diets, refusals, and fecal specimens (fresh, dry-only, and dried/ground) using atomic absorption to detect Cr and spectrophotometry for Ti. Concentration of both markers was also determined via the PXRF spectrometer. Delta between ATTD estimated by wet chemistry and PXRF was not different from zero ( P ≥ 0.14) when using cattle fresh fecal specimens for both markers, whereas ATTD estimated by PXRF with dry-only and dried/ground fecal specimens were 3.6 and 1.1 percent units lower ( P ≤ 0.04), respectively, than ATTD estimated by wet chemistry for Cr and Ti, respectively. Regardless of the fecal sample preparation method on cattle specimens, Ti concentration was similar ( P = 0.39) among methodologies, while Cr was underestimated ( P < 0.01) by 13% when PXRF was used in dry-only or dried/ground samples. The ATTD of sheep was underestimated ( P < 0.01) by 2.4 percent units compared with control when Cr was measured by PXRF in dry-only samples. The Cr concentration in dry-only fecal specimens of sheep tended ( P = 0.09) to be lower compared with wet chemistry analysis. Fresh and dry/ground sheep fecal samples assessed for Cr, and dry-only assessed for Ti were not ( P ≥ 0.49) affected by detection method. The Cr fecal recovery tended ( P = 0.10) to be the lowest for dry-only, the greatest for wet chemistry, intermediate for fresh and dry/ground sheep-fecal specimens; while not affected ( P = 0.40) for Ti. The PXRF is an accurate technology to detect Cr and Ti in fresh cattle fecal samples to estimate ATTD. For fresh and dry/ground, the technology was effective for determining the concentration of Cr, or dry-only fecal specimens when detecting Ti in sheep specimens.